Safety evaluation of the food enzyme triacylglycerol lipase from the non‐genetically modified Limtongozyma cylindracea strain AE‐LAYH (B) - EFSA Panel on Food Enzymes (FEZ); José Manuel Barat Baviera; Claudia Bolognesi; Francesco Catania; Gabriele Gadermaier; Ralf Greiner; Baltasar Mayo; Alicja Mortensen; Yrjö Henrik Roos; Marize L. M. Solano; Monika Sramkova; Henk Van Loveren; et al. (EFSA Journal)
Abstract The food enzyme, a triacylglycerol lipase (triacylglycerol acylhydrolase; EC 3.1.1.3), is produced with the non‐genetically modified Limtongozyma cylindracea strain AE‐LAYH (B) by Amano Enzyme Inc. It is intended to be used in six food manufacturing processes. Since residual amounts of food enzyme–total organic solids (TOS) are removed in one process, dietary exposure was calculated only for the remaining five food manufacturing processes. It was estimated to be up to 0.315 mg TOS/kg body weight (bw) per day in European populations. As the production strain qualifies for the quality presumption of safety (QPS) approach of safety assessment and no issue of concern arising from the production process of the food enzyme were identified, the Panel considered that no toxicological studies other than the assessment of allergenicity were necessary. A homology search for the amino acid sequence of the food enzyme to those of known allergens was made and one match with a honeybee venom allergen was found. The Panel considered that a risk of allergic reactions by dietary exposure, particularly in individuals allergic to honey, cannot be excluded, but is considered to be low. Based on the data provided, the QPS status of the production strain and the absence of issues of concern arising from the food enzyme manufacturing process, the Panel concluded that this food enzyme does not give rise to safety concerns under the intended conditions of use.